Mineral Magnetism of Environmental Reference Materials: Iron Oxyhydroxide Nanoparticles - Gonzalez-Lucena, Fedora (University of Ottawa (Canada), 2010)
Iron oxyhydroxides are ubiquitous in surface environments, playing a key role in many biogeochemical processes. Their characterization is made challenging by their nanophase nature. Magnetometry serves as a sensitive non-destructive characterization technique that can elucidate intrinsic physical properties, taking advantage of the superparamagnetic behaviour that nanoparticles may exhibit. In this work, synthetic analogues of common iron oxyhydroxide minerals (ferrihydrite, goethite, lepidocrocite, schwertmannite and akaganeite) are characterized using DC and AC magnetometry (cryogenic, room temperature), along with complementary analyses from Mossbauer spectroscopy (cryogenic, room temperature), powder X-ray diffraction and scanning electron microscopy. It was found that all of the iron oxyhydroxide mineral nanoparticles, including lepidocrocite, schwertmannite and akaganeite were superparamagnetic and therefore magnetically ordered at room temperature. Previous estimates of Neel temperatures for these three minerals are relatively low and are understood as misinterpreted magnetic blocking temperatures. This has important implications in environmental geoscience due to this mineral group's potential as magnetic remanence carriers. Analysis of the data enabled the extraction of the intrinsic physical parameters of the nanoparticles, including magnetic sizes. The study also showed the possible effect on these parameters of crystal-chemical variations, due to elemental structural incorporation, providing a nanoscale mineralogical characterization of these iron oxyhydroxides. The analysis of the intrinsic parameters showed that all of the iron oxyhydroxide mineral nanoparticles considered here have a common magnetic moment formation mechanism associated with a random spatial distribution of uncompensated magnetic spins, and with different degrees of structural disorder and compositional stoichiometry variability, which give rise to relatively large intrinsic magnetization values. The elucidation of the magnetic nanostructure also contributes to the study of the surface region of the nanoparticles, which affects the particles' reactivity in the environment.
Keywords: Geology.; Mineralogy.